Description of a new species of the genus Paralecanium Cockerell & Bueker (Hemiptera: Coccomorpha: Coccidae) from China - Tan, Zhixiang; Meng, Shitao; Xing, Jichun (Zootaxa, 2024)
A new species of soft scale insect (Hemiptera: Coccomorpha: Coccidae) belonging to the genus Paralecanium Cockerell & Bueker, P. sabia Tan, Meng & Xing sp. n., is described and illustrated. It was found on the leaves of Sabia swinhoei Hemsl (Sabiaceae) in Guizhou Maolan National Nature Reserve, Guizhou Province, China. Habitat photographs and illustrations are provided. The type material of P. sabia sp. n. is deposited at the Institute of Entomology, Guizhou University, Guiyang, China (GUGC) and in the insect collection at the Department of Forestry Protection, Beijing Forestry University, Beijing, China (NFUC). An identification key to separate the 28 species in Paralecanium, based on the morphology of adult females, is provided.